The Effect Of Workload And Digital Competence on The Performance of Non-Lecturing Staff at Open University of Bandung in Facing Era 4.0 - Rakhmayati, Eka Nur; Sondari, Mery Citra; Kusnendi, Kusnendi (Jurnal Wacana Ekonomi, 2024)
Open University as a pioneer in the midst of distance education competition in the country is expected to remain at the forefront in providing distance education services. The purpose of this study is to analyze the effect of workload on the performance of non-teaching staff at Open University of Bandung and the effect of digital competence on the performance of non-teaching staff at Open University of Bandung. This research approach employs quantitative methods and correlational research methods. The object of this research is the Open University. While the subjects are non-teaching staff at Open University of Bandung. Research findings results are, when it comes to competing for distance higher education services in the 4.0 era, workload affects the performance of non-teaching staff at the Open University of Bandung. Digital competence has a positive effect on the performance of non-teaching staff at Open University of Bandung when faced with competition for distance higher education services in the 4.0 era.